Vulnerabilität, Demokratie, politische Interessen? - Betzold, Carola (Zeitschrift für internationale Beziehungen, 2015)
Germany - one of the largest donors in the field of climate finance - promises to prioritise the most vulnerable and poorest countries in its financial contribution for climate change adaptation. But to what extent does Germany keep its promise? Who receives German adaptation aid and why? This article analyses statistically how Germany allocated its bilateral adaptation aid from 2010 to 2012. The results suggest only a weak link between need - that is, vulnerability to climate change - and the level of adaptation aid a country receives. While poorer countries receive relatively more adaptation aid, other vulnerability indicators do not seem to matter - as opposed to economic and political factors. The results reflect not least that vulnerability is a complex concept that is difficult to measure; the question who is particularly vulnerable is fundamentally a normative decision. Keywords: adaptation, aid allocation, Germany, climate change. (Zeitschrift für Internationale Beziehungen / SWP)